Outcomes after culprit-only percutaneous coronary intervention for multivessel disease during ST-segment elevation myocardial infarction: a comparison of registry and clinical trial outcomes. Issue 7 (November 2018) - Jackson, Matthew W.P.; Austin, David; Swanson, Neil; Williams, Paul D.; Muir, Douglas F.; Hall, Jim A.; Wright, Robert A.; Sutton, Andrew G.C.; Carter, Justin; de Belder, Mark A.
Abstract : Background: The PRAMI and CvLPRIT trials support preventive percutaneous coronary intervention (PCI) for multivessel coronary disease found during ST-segment elevation myocardial infarction (STEMI). We assess our real-world experience of the management of multivessel disease identified during primary PCI (PPCI) in a large UK regional centre. Patients and methods: All STEMI patients who underwent culprit-only PPCI during the study period (August 2011 to August 2013) were retrospectively assessed for eligibility to each trial. The two resulting groups were designated as the 'observational' cohorts. Primary outcomes were then determined and compared with the culprit-only revascularisation cohorts from the respective published randomized controlled trials (RCTs). Results: A total of 1143 consecutive cases were presented during the study period. Of these, 343 would have been suitable for inclusion to PRAMI and were included in the 'observational PRAMI' cohort; 196 patients were included in the 'observational CvLPRIT' cohort. The 'observational PRAMI' cohort experienced fewer primary outcome events (13.1 vs. 22.9%), cardiac deaths (0.6 vs. 4.3%) and nonfatal myocardial infarctions (3.5 vs. 8.7%) than the culprit-only PCI PRAMI cohort ( n =231); there were significantly more diabetics ( P =0.022) and anterior STEMI initial presentations in the culprit-only PCI PRAMI cohort. Primary outcomes were comparable to those of the preventive PCI PRAMI cohort. The 'observational CvLPRIT' cohort showed no significant difference in primary outcomes over 12 months (16.8 vs. 21.2%), but significantly lower all-cause mortality (2 vs. 6.9%) than the culprit-only PCI CvPLRIT cohort ( n =146). The 30-day event rates were similar to the preventive PCI arm; the 12-month events were better than the nonpreventive, but not as good as the preventive RCT cohorts. Conclusion: Outcomes from culprit-only primary PCI for multivessel disease in patients selected by the RCT criteria from an all-comers population representing real-life experience are better than those published in the two main RCTs. The RCTs may have selected a high-risk population for study exaggerating the benefits of preventive PCI.